THE EFFECTIVENESS OF DICTOGLOSS IN TEACHING LISTENING COMPREHENSION - Ahmad Salman Arrofi; Aunurrahman; Finny Anita (Program Studi Pendidikan Bahasa Inggris, 2025)
Listening comprehension involves understanding spoken language in real time, yet it is often underemphasized in classrooms. This study examined the effectiveness of the Dictogloss technique in teaching listening comprehension among 25 tenth-grade students at SMA Negeri 2 Selakau in the 2024/2025 academic year. Using a one-group pre-test and post-test design over four sessions, data were collected through listening tests based on dialogue texts. Results showed an improvement in listening for details, with mean scores rising from 50 to 65.6 (a 31.2% increase). However, accuracy of answers declined from 44 to 36 (an 18.18% decrease). Overall, the average score increased from 47 to 50.8. Despite these changes, the Wilcoxon Signed-Rank test indicated no statistically significant effect (p = 0.153), and the small effect size (Cohen’s d = 0.271) suggested the Dictogloss technique had a limited impact. Keywords: Listening for Details, Accuracy of Answers, Dictogloss, Listening comprehension